Facilitating and Regulating Commerce - the Court Process - Galbraith, Alan (Victoria University of Wellington Law Review, 2002)
The paper argues that commercial litigation is not handled efficiently in the court system and suggests some improvements that can be made to the current court system. The author discusses the quality of commercial decisions in our current system, who those decision-makers are, the methodology of the decision-making process, and the overall efficiency of the process. Galbraith QC argues that the structure of our current court system will not always result in the right outcome in commercial disputes. For example, the old Commercial List did not allow Commercial List Judges to determine which cases were of sufficient commercial significance to be substantively adjudicated upon by a Commercial List Judge, resulting in inefficiency. The author also laments the lack of empirical economic evidence in commercial judgments.